2022 Expert consensus on the use of laser ablation for papillary thyroid microcarcinoma. (31st December 2022) - Zhang, Lu; Zhou, Wei; Zhou, Jian Qiao; Shi, Qian; Rago, Teresa; Gambelunghe, Giovanni; Zou, Da Zhong; Gu, Jun; Lu, Man; Chen, Fen; Ren, Jie; Cheng, Wen; et al.
Abstract: Objective: With the aim of standardizing and improving the use of ultrasound-guided PLA on PTMC, a panel of experts from China and Italy, jointly issued this expert consensus on the clinical use of PLA for low-risk PTMC. Methods: This expert consensus was developed by Chinese and Italian experts who have specific competence and expertise in this area. An evidence-based approach combining the knowledge and practical experience of the panelists was utilized. Results: Twenty-six expert consensus recommendations were developed, spanning topics including the indications and contraindications of PLA for PTMC, physician training, preoperative preparation of patients, intraoperative technical procedures, possible complications, efficacy assessment, follow-up strategy, the approach to new PTMC and metastatic lymph nodes after treatment, thyroid-stimulating hormone inhibition therapy, and quality control of the entire procedure. Conclusion: We summarized practical recommendations about standardized and improved PLA treatment for PTMC.